Understanding High Anisotropic Magnetism by Ultrathin Shell Layer Formation for Magnetically Hard-Soft Core-Shell Nanostructures - Lee, Kwan; Lee, Sangyeob; Ahn, Byungmin (Chemistry of Materials, 2019)
Magnetic core-shell nanostructures offer a viable solution for tunable magnetism via nanoscale exchange interactions in a single-component unit. A typical synthetic approach for monodisperse bimagnetic ferrite core-shell nanostructures employs the seed-mediated growth method using the heating-up process. Understanding magnetic core-shell interface formation and their interactions is crucial; however, the magnetical persistence of the pristine core component during the heating-up process is unclear. Here, we elucidate the enhancement mechanism of magnetic anisotropy when the hard-soft core-shell nanostructures are formed with the ultrathin shell layer. The heating-up effect on the core component exhibits the coordination change of ligand chemisorption with surface metal ions, which leads to a substantial increase in surface anisotropy due to enhanced spin-orbit couplings. We further demonstrate that the selection of metal precursors and surfactants for additional shell layer formation is important. The kinetic of the shell formation rate by their thermolysis and atomic-scale surface etching by the surfactant led to the disordering of surface spins on the core parts. Our observations provide the underlying mechanism of high anisotropic magnetism while bimagnetic ferrite core-shell interface formation and the voyage of synthetic procedures for the additional shell layer are critical to an outcoming magnetism.
Keywords: Coordination change; Core shell nano structures; Core-shell interface; Enhancement mechanism; Seed-mediated growth methods; Spin-orbit couplings; Synthetic approach; Synthetic procedures